PENGARUH LINGKUNGAN GURU PAI DALAM MEMBENTUK KEPRIBADIAN ISLAM SISWA MADRASAH AL-FURQON KABUPATEN BANDUNG: Lingkungan Guru PAI dan Pembentukan Kepribadian Islam Siswa: Analisis Peran, Tantangan, dan Strategi - Suryani, Eke; Murtadlo, Muhammad Ali; Kurniawan, Wakib (CV. Media Publikasi Profesional, 2025)
In an era where rapid digitalization and the pervasive influence of social media increasingly weaken moral authority within educational settings, the need to develop students’ Islamic personality has become more urgent than ever. Within this context, the PAI (Islamic Religious Education) teacher environment holds a pivotal role as a source of moral modeling, habituation, and educational interaction that directly shapes students’ religious character. This study aims to analyze the role of the PAI teacher environment in shaping students’ Islamic personality, as well as to identify the challenges encountered and the strategies implemented by teachers in this process. Employing a descriptive qualitative approach, data were collected through observations, interviews, and documentation. The findings reveal that the PAI teacher environment contributes significantly to the formation of students’ Islamic personality through moral exemplification, the habituation of Islamic values, meaningful educational communication, and student engagement in religious activities. The main challenges include the influence of social media, students’ inconsistency in practicing Islamic values, and varied levels of family support. Effective strategies consist of integrating Islamic values into instruction, strengthening the school’s Islamic culture, and fostering emotional closeness between teachers and students. This study contributes a conceptual model highlighting the strategic role of the PAI teacher environment in shaping students’ Islamic personality and offers practical recommendations for educational institutions seeking to enhance the quality of Islamic education.